A kind of all-solid waste antifreeze permeable brick and its preparation method and application
Through the preparation method of all-solid waste anti-freeze permeable bricks, waste concrete coarse aggregate and tailings machine-made sand and other materials are used to form interconnected permeable pores and dense layers, which solves the problem of reduced compressive strength and flexural strength of permeable bricks and achieves the effects of high permeability, high mechanical strength and high frost resistance.
Patent Information
- Application Number
- CN202310752726.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2025-09-16
- Estimated Expiration
- 2043-06-26
AI Technical Summary
After the existing permeable bricks replaced natural river sand with tailings machine-made sand, the compressive strength and flexural strength decreased, making it difficult to meet market demand.
The preparation method of all-solid waste anti-freeze permeable bricks is adopted. Through the combination of base layer and surface layer, waste concrete coarse aggregate, tailings machine-made sand, polypropylene fiber, surface modified tailings machine-made sand, acrylic polymer emulsion and phase change energy storage material are used to form interconnected permeable pores and dense layers to enhance mechanical strength and frost resistance.
The permeable bricks have achieved high permeability, high mechanical strength and high frost resistance, with a permeability coefficient of >2mm/s, 28d compressive strength >45MPa, 28d flexural strength >5MPa, and compressive strength loss rate after 50 freeze-thaw cycles <34%, meeting market demand.
Smart Images

Figure BDA0004301698250000061 
Figure BDA0004301698250000062 
Figure BDA0004301698250000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of permeable bricks, and more specifically, to an all-solid waste antifreeze permeable brick and a preparation method and application thereof. Background Art
[0002] Permeable bricks are a type of brick material with excellent water permeability. They can effectively absorb excess water and drain it underground, reducing water accumulation on the road surface. They have been widely used in urban road construction. Common permeable bricks include concrete permeable bricks, polymer fiber concrete permeable bricks, colored stone composite concrete permeable bricks, colored stone epoxy permeable bricks, and ecological sand-based permeable bricks.
[0003] The ecological sand-based permeable bricks in the existing technology generally include a base layer and a surface layer. The base layer is mainly made of water, cement, gravel, sand, and a water reducer; the surface layer is mainly made of water, cement, natural river sand, and a water reducer. However, natural river sand is a non-renewable resource and its quantity is limited. There are a large number of tailings machine-made sands in China. If tailings machine-made sands are used in permeable bricks, it can not only reduce the pollution of tailings machine-made sands to the environment, but also reduce the use of natural river sands. The applicant found in actual processing that if tailings machine-made sands are used to replace natural river sands, and as the weight ratio of tailings machine-made sands to natural river sands continues to increase, the compressive strength and flexural strength of the permeable bricks continue to decrease. In order to fully utilize the tailings machine-made sands, how to improve the compressive strength and flexural strength of the permeable bricks on the basis of completely replacing the natural river sands with tailings machine-made sands has become an urgent problem to be solved. Summary of the Invention
[0004] On the basis of completely replacing natural river sand with tailings machine-made sand, in order to improve the compressive strength and flexural strength of permeable bricks, the present application provides a full-solid waste antifreeze permeable brick and its preparation method and application.
[0005] In the first aspect, the present application provides an all-solid waste antifreeze permeable brick, which adopts the following technical solution:
[0006] A full solid waste antifreeze permeable brick, comprising a base layer and a surface layer arranged on the surface of the base layer;
[0007] The base layer is mainly made of the following raw materials in parts by weight: 5-15 parts of water, 15-20 parts of cement, 2-5 parts of fly ash, 55-70 parts of waste concrete coarse aggregate, 10-15 parts of tailings machine-made sand, 0.2-0.4 parts of polypropylene fiber, and 0.1-0.3 parts of water reducer;
[0008] The surface layer is mainly made of the following raw materials in parts by weight: 5-15 parts of water, 25-50 parts of cement, 3-6 parts of fly ash, 40-55 parts of surface-modified tailings machine-made sand, 1-2 parts of acrylic polymer emulsion, 0.4-0.6 parts of adipic acid dihydrazide, 10-15 parts of phase change energy storage material, and 0.1-0.3 parts of water reducer;
[0009] The surface-modified tailings machine-made sand is obtained by treating tailings machine-made sand with γ-methacryloxypropyltrimethoxysilane, oleic acid acylpropyl dimethyl betaine, and diacetone acrylamide.
[0010] By adopting the above technical solution, among the raw materials for the base layer, waste concrete coarse aggregate is obtained by processing waste concrete, and tailings machine-made sand is obtained by processing tailings. Since waste concrete and tailings are both solid wastes, at this time, not only is their pollution to the environment reduced, but also solid waste recycling is achieved. Moreover, the mutual cooperation between waste concrete coarse aggregate and tailings machine-made sand is used to form interconnected permeable pores, so that the permeable bricks maintain good permeability. At the same time, polypropylene fiber is also added to the raw materials to reduce the impact of waste concrete coarse aggregate and tailings machine-made sand on the mechanical strength of the base layer and enhance the service life of the permeable bricks. Among the raw materials for the surface layer, surface-modified tailings machine-made sand is used to form a dense layer with good permeability and air permeability, and can also reduce the blockage of mud, ash, and small objects in the interconnected permeable pores of the base layer, so that the permeable bricks maintain good permeability as a whole. The permeable bricks of the present application, through the interaction between the base layer and the surface layer, the synergistic efficiency of the base layer raw materials, and the synergistic efficiency of the surface layer raw materials, make the permeable bricks have a permeability coefficient greater than 2mm / s, 28d compressive strength greater than 45MPa, 28d flexural strength greater than 5MPa, and a compressive strength loss rate of less than 34% after 50 freeze-thaw cycles, so that the permeable bricks exhibit the characteristics of high permeability, high mechanical strength, and high frost resistance, meeting market demand.
[0011] Acrylic polymer emulsion and phase-change energy storage material are added to the surface layer raw materials. The acrylic polymer emulsion loses water to form acrylic polymer, which, when combined with cement and fly ash, can achieve bonding between the surface-modified tailings and machine-made sand, forming a mesh structure and enhancing the mechanical strength of the permeable bricks. Furthermore, when the permeable bricks expand and contract due to changes in ambient temperature, the acrylic polymer can effectively reduce the internal stress of the permeable bricks, improving their frost resistance. The phase-change energy storage material can reduce the impact of ambient temperature changes on the permeable bricks and, when combined with the acrylic polymer, further enhance their frost resistance.
[0012] In the surface layer raw materials, γ-methacryloyloxypropyl trimethoxysilane, oleic acid acylpropyl dimethyl betaine, and diacetone acrylamide are also used to treat the tailings machine-made sand. Silicon groups, ester groups, imide groups, zwitterionic betaine groups, and ketone carbonyl groups are introduced to the surface of the tailings machine-made sand, effectively increasing the connection strength between the tailings machine-made sand and the polypropylene polymer and increasing the use effect of the acrylic polymer emulsion. In addition, adipic acid dihydrazide is added to the raw materials. Adipic acid dihydrazide contains two hydrazide groups, and the surface of the surface-modified tailings machine-made sand contains ketone carbonyl groups. The two can undergo a self-crosslinking reaction, further enhancing the interaction between the surface-modified tailings machine-made sand and the polypropylene polymer, improving the mechanical strength and frost resistance of the permeable bricks, and making the permeable bricks exhibit better comprehensive performance.
[0013] Optionally, the surface-modified tailings machine-made sand is prepared by the following method: adding γ-methacryloyloxypropyltrimethoxysilane, oleic acid acylpropyl dimethyl betaine, and diacetone acrylamide to water, mixing, then adding tailings machine-made sand, stirring for 0.5-1.5 hours, then adding ammonium persulfate, stirring for 9-11 hours, filtering, washing, and drying to obtain surface-modified tailings machine-made sand.
[0014] Optionally, in the surface-modified tailings machine-made sand, the weight ratio of tailings machine-made sand, γ-methacryloxypropyltrimethoxysilane, oleic acid acylpropyl dimethyl betaine, and diacetone acrylamide is 100:(2-4):(2-4):(0.5-1.5).
[0015] By adopting the above technical scheme, γ-methacryloyloxypropyltrimethoxysilane, oleic acid acylpropyl dimethyl betaine, and diacetone acrylamide are first grafted on the surface of the tailings machine-made sand, and then ammonium persulfate is added, which can generate free radicals. The free radicals excite monomers to copolymerize on the surface of the tailings machine-made sand, and introduce siloxy groups, ester groups, imide groups, zwitterionic betaine groups, and ketone carbonyl groups on the surface of the tailings machine-made sand, thereby increasing the interaction between the surface-modified tailings machine-made sand and the acrylic polymer, improving the connection strength of the surface layer raw materials, and enhancing the mechanical strength and frost resistance of the permeable bricks.
[0016] Furthermore, in the surface-modified tailings machine-made sand, the weight ratio of tailings machine-made sand, water, and ammonium persulfate is 100:(500-1500):(0.3-0.8).
[0017] Optionally, the phase change energy storage material is one or more of phase change microcapsules MPCM5, phase change microcapsules MPCM28H, phase change microcapsules MPCM38, and phase change microcapsules MPCM48.
[0018] The phase change microcapsule MPCM5 has a wax capsule structure, with a core material of n-tetradecane and a shell material of melamine urea-formaldehyde resin. The phase change temperature is 5°C and the latent heat value is 190-200 joules / g. The phase change microcapsule MPCM28H also has a wax capsule structure, with a core material of n-octadecane and a shell material of melamine urea-formaldehyde resin. The phase change temperature is 28°C and the latent heat value is 190-200 joules / g. The phase change microcapsule MPCM38 also has a wax capsule structure, with a core material of biomass phase change wax and a shell material of melamine urea-formaldehyde resin. The phase change temperature is 38°C and the latent heat value is 190-200 joules / g. The phase change microcapsule MPCM48 also has a wax capsule structure, with a core material of biomass phase change wax and a shell material of melamine urea-formaldehyde resin. The phase change temperature is 5°C and the latent heat value is 190-200 joules / g. Optimizing the phase change energy storage material facilitates the selection of the phase change energy storage material. Moreover, since the phase change energy storage material is a wax capsule structure, the phase change wax is coated with a shell material to reduce the loss of the phase change wax. The phase change of the phase change wax is utilized to maintain a good use effect of the phase change energy storage material.
[0019] Optionally, the phase change energy storage materials are two types of phase change microcapsules MPCM5 and phase change microcapsules MPCM38, and the weight ratio of phase change microcapsules MPCM5 and phase change microcapsules MPCM38 is (1-3):(1-3).
[0020] By adopting the above technical solution, the phase change energy storage materials are two types: phase change microcapsules MPCM5 and phase change microcapsules MPCM38. The phase change temperature of the phase change microcapsules MPCM5 is 5°C, which reduces the cracking of the permeable bricks caused by low ambient temperatures in winter. Furthermore, the phase change temperature of the phase change microcapsules MPCM38 is 38°C, which reduces the oxidation of the permeable bricks caused by high ambient temperatures in summer. At the same time, the synergistic effect between the phase change microcapsules MPCM5 and MPCM38 is also utilized to reduce the temperature changes caused by cement hydration during the curing process of the permeable bricks, reduce temperature stress, improve the mechanical strength of the permeable bricks, and extend the permeability service life.
[0021] In a plurality of technical solutions, the weight ratio of the phase change microcapsules MPCM5 and the phase change microcapsules MPCM38 is 1:1. The weight ratio can also be set to 1:2, 1:3, 2:1, 2:3, 3:1, 3:2, etc. as needed.
[0022] Optionally, the particle size of the waste concrete coarse aggregate is continuously graded from 1 to 10 mm; and the particle size of the tailings machine-made sand is continuously graded from 0.25 to 0.5 mm.
[0023] By adopting the above technical solution, the particle size of waste concrete coarse aggregate and tailings machine-made sand is optimized. By utilizing the mutual coordination of waste concrete coarse aggregate of different particle sizes and tailings machine-made sand of different particle sizes, the raw materials of the foundation maintain good fluidity on the basis of maintaining good permeability of the permeable bricks, and the density of the base layer is increased, thereby improving the mechanical strength of the permeable bricks.
[0024] Furthermore, the cement is ordinary Portland cement. The fly ash is Class I fly ash. The tailings manufactured sand is iron tailings manufactured sand. The water reducer is a polycarboxylate water reducer. The acrylic polymer emulsion is LEAC acrylic polymer emulsion. The polypropylene fibers have an average length of 1-5 mm and an average diameter of 0.1-0.5 mm.
[0025] Optionally, the thickness of the base layer is 50-100 mm; the thickness of the surface layer is 5-10 mm.
[0026] By adopting the above technical solution, the thickness of the base layer and the surface layer is optimized, so that the permeable bricks maintain good permeability and mechanical strength.
[0027] In a plurality of embodiments, the thickness of the base layer is 80 mm and the thickness of the surface layer is 8 mm. The thickness of the base layer can also be set to 50 mm, 60 mm, 70 mm, 90 mm, 100 mm, etc. as needed. The thickness of the surface layer can also be set to 5 mm, 6 mm, 7 mm, 9 mm, 10 mm, etc. as needed.
[0028] In a second aspect, the present application provides a method for preparing the above-mentioned all-solid waste antifreeze permeable bricks, which adopts the following technical solution:
[0029] A method for preparing the above-mentioned all-solid waste antifreeze permeable bricks comprises the following steps:
[0030] S1. Prepare base course mixture and surface course mixture;
[0031] The base mixture is prepared by the following method: water, cement, fly ash, waste concrete coarse aggregate, tailings machine-made sand, polypropylene fiber, and water reducing agent are mixed to obtain the base mixture;
[0032] The surface layer mixture is prepared by the following method: water, cement, fly ash, surface modified tailings machine-made sand, acrylic polymer emulsion, adipic acid dihydrazide, phase change energy storage material, and water reducing agent are mixed to obtain the surface layer mixture;
[0033] S2, pouring the base mixture into a mold, vibrating, and pressing to obtain a semi-finished product;
[0034] S3. Spread the surface mixture on the surface of the semi-finished product, vibrate, press, and cure to obtain permeable bricks.
[0035] By adopting the above technical solution, the base layer mixture and the surface layer mixture are prepared in advance, and then the base layer mixture is spread, and then the surface layer mixture is spread, and vibration and pressing are combined, which not only reduces the hollowing phenomenon, but also makes the base layer and the surface layer in close contact, enhances the connection strength between the base layer and the surface layer, and improves the service life of the permeable bricks.
[0036] Optionally, in step S2, the vibration frequency is 500-700 Hz, the vibration time is 3-5 s, the pressing pressure is 0.11-0.13 MPa, and the pressing time is 1-3 s;
[0037] In step S3, the vibration frequency is 700-900 Hz, the vibration time is 5-7 s, the pressing pressure is 0.11-0.13 MPa, and the pressing time is 2-4 s.
[0038] By adopting the above technical solution, the vibration frequency, vibration time, pressing pressure and pressing time in step S2 and step S3 are optimized, which facilitates the preparation of permeable bricks.
[0039] In various embodiments, in step S2, the vibration frequency is 600 Hz, the vibration time is 4 seconds, the pressing pressure is 0.12 MPa, and the pressing time is 2 seconds. The vibration frequency can also be set to 500 Hz, 700 Hz, etc. as needed. The vibration time can also be set to 3 seconds, 5 seconds, etc. as needed. The pressing pressure can also be set to 0.11 MPa, 0.13 MPa, etc. as needed. The pressing time can also be set to 1 second, 3 seconds, etc. as needed.
[0040] In various embodiments, in step S3, the vibration frequency is 800 Hz, the vibration time is 6 seconds, the pressing pressure is 0.12 MPa, and the pressing time is 3 seconds. The vibration frequency can also be set to 700 Hz, 900 Hz, etc., as needed. The vibration time can also be set to 5 seconds, 7 seconds, etc., as needed. The pressing pressure can also be set to 0.11 MPa, 0.13 MPa, etc., as needed. The pressing time can also be set to 2 seconds, 4 seconds, etc., as needed.
[0041] In a third aspect, the present application provides an application of the above-mentioned all-solid waste antifreeze permeable bricks in road construction.
[0042] In summary, this application has at least the following beneficial effects:
[0043] 1. The all-solid waste antifreeze permeable bricks of this application, through the interaction between the base layer and the surface layer, the synergistic efficiency of the base layer raw materials, and the synergistic efficiency of the surface layer raw materials, make the permeable bricks have a permeability coefficient greater than 2mm / s, 28d compressive strength greater than 45MPa, 28d flexural strength greater than 5MPa, and the compressive strength loss rate after 50 freeze-thaw cycles less than 34%, so that the permeable bricks exhibit the characteristics of high permeability, high mechanical strength, and high frost resistance, meeting market demand.
[0044] 2. The surface-modified tailings machine-made sand of the present application uses γ-methacryloyloxypropyltrimethoxysilane, oleic acid acylpropyl dimethyl betaine, and diacetone acrylamide to treat the tailings machine-made sand, introducing siloxy groups, ester groups, imide groups, zwitterionic betaine groups, and ketone carbonyl groups on the surface of the tailings machine-made sand to increase the connection strength between the tailings machine-made sand and the polypropylene polymer. In addition, in combination with adipic acid dihydrazide, the hydrazide groups in adipic acid dihydrazide and the ketone carbonyl groups on the surface of the surface-modified tailings machine-made sand undergo self-crosslinking, further enhancing the interaction between the surface-modified tailings machine-made sand and the polypropylene polymer, enhancing the use effect of the acrylic polymer emulsion, improving the mechanical strength and frost resistance of the permeable bricks, and making the permeable bricks exhibit better comprehensive performance. DETAILED DESCRIPTION
[0045] To make this application easier to understand, the following examples will be used to further illustrate this application. These examples are for illustrative purposes only and are not intended to limit the scope of application of this application. Unless otherwise specified, the raw materials or components used in this application can be obtained through commercial channels or conventional methods.
[0046] Preparation Example
[0047] Preparation Example 1
[0048] A surface-modified tailings machine-made sand is prepared by the following method:
[0049] 3 kg of γ-methacryloyloxypropyltrimethoxysilane, 3 kg of oleoylpropyl dimethyl betaine, and 1 kg of diacetone acrylamide were added to 1000 kg of water and stirred for 30 minutes. Then, 100 kg of tailings manufactured sand was added and stirred for 1 hour. 0.5 kg of ammonium persulfate was added and stirred for 10 hours. The mixture was filtered, washed three times with 300 kg of water each time, and dried to obtain surface-modified tailings manufactured sand.
[0050] Preparation Example 2
[0051] A surface-modified tailings machine-made sand is prepared by the following method:
[0052] 2 kg of γ-methacryloyloxypropyltrimethoxysilane, 4 kg of oleoylpropyldimethylbetaine, and 0.5 kg of diacetone acrylamide were added to 500 kg of water and stirred for 30 minutes. Then, 100 kg of tailings manufactured sand was added and stirred for 0.5 hours. Then, 0.3 kg of ammonium persulfate was added and stirred for 9 hours. The mixture was filtered, washed three times with 300 kg of water each time, and dried to obtain surface-modified tailings manufactured sand.
[0053] Preparation Example 3
[0054] A surface-modified tailings machine-made sand is prepared by the following method:
[0055] 4 kg of γ-methacryloyloxypropyltrimethoxysilane, 2 kg of oleacylpropyl dimethyl betaine, and 1.5 kg of diacetone acrylamide were added to 1500 kg of water and stirred for 30 minutes. Then, 100 kg of tailings manufactured sand was added and stirred for 1.5 hours. 0.8 kg of ammonium persulfate was added and stirred for 11 hours. The mixture was filtered, washed three times with 300 kg of water each time, and dried to obtain surface-modified tailings manufactured sand.
[0056] Example
[0057] Table 1 Raw material content of base layer (unit: kg)
[0058]
[0059] Table 2 Raw material content of acidic iron-carrying molten phase (unit: kg)
[0060]
[0061]
[0062] Example 1
[0063] A fully solid waste frost-resistant permeable brick comprises a base layer and a surface layer disposed on the surface of the base layer. The base layer is 80 mm thick, and the surface layer is 8 mm thick. The raw materials and their proportions for the base layer are shown in Table 1, and the raw materials and their proportions for the surface layer are shown in Table 2.
[0064] Among them, the cement is ordinary Portland cement, specifically ordinary Portland cement P.O42.5; the fly ash is Class I fly ash; the waste concrete coarse aggregate is construction concrete waste, and the particle size of the waste concrete coarse aggregate is 1-10mm continuously graded; the tailings machine-made sand is iron tailings machine-made sand, and the particle size of the tailings machine-made sand is 0.25-0.5mm continuously graded; the average length of the polypropylene fiber is 3mm and the average diameter is 0.3mm; the water reducer is a polycarboxylic acid water reducer, specifically polycarboxylic acid water reducer AN4000; the acrylic polymer emulsion is LEAC acrylic polymer emulsion, and is selected from LEAC-21 of Beijing China Nuclear North Research Institute Technology Development Co., Ltd.; the surface-modified tailings machine-made sand is prepared by Preparation Example 1.
[0065] The phase-change energy storage materials are MPCM5 and MPCM38, with a weight ratio of 1:1. Both MPCM5 and MPCM38 are sourced from Shanghai Ruentropy New Energy Technology Co., Ltd.
[0066] A method for preparing all-solid waste antifreeze permeable bricks, comprising the following steps:
[0067] S1. Prepare base layer mixture and surface layer mixture.
[0068] The base mix was prepared using the following method: tailings sand was added to waste concrete coarse aggregate and stirred for 5 minutes. Cement, fly ash, and polypropylene fiber were then added and stirred for 5 minutes. Water and a water reducer were then added and stirred for 20 minutes to obtain the base mix.
[0069] The surface layer mixture was prepared by adding cement, fly ash, and phase change energy storage material to surface-modified tailings machine-made sand and stirring for 5 minutes. Water, a water reducer, acrylic polymer emulsion, and adipic acid dihydrazide were then added and stirred for 20 minutes to obtain the surface layer mixture.
[0070] S2. Pour the base mixture into a mold, vibrate it at a frequency of 600 Hz for 4 seconds, and then press it at a pressure of 0.12 MPa for 2 seconds to obtain a semi-finished product.
[0071] S3. Spread the surface layer mixture on the semi-finished product and vibrate it at a frequency of 800 Hz for 6 seconds. Then, press it at a pressure of 0.12 MPa for 3 seconds. Then, cure it at a temperature of 25°C and a humidity of 90% for 28 days. At this point, the base layer mixture has solidified to form the base layer, and the surface layer mixture has solidified to form the surface layer. Finally, permeable bricks are obtained.
[0072] Example 2
[0073] A fully solid waste antifreeze permeable brick, which differs from Example 1 in that the raw material ratios of the base layer and the surface layer are different, and the raw materials and raw material ratios of the base layer are shown in Table 1, and the raw materials and raw material ratios of the surface layer are shown in Table 2.
[0074] Example 3
[0075] A fully solid waste antifreeze permeable brick, which differs from Example 1 in that the raw material ratios of the base layer and the surface layer are different, and the raw materials and raw material ratios of the base layer are shown in Table 1, and the raw materials and raw material ratios of the surface layer are shown in Table 2.
[0076] Example 4
[0077] A fully solid waste antifreeze permeable brick, which differs from Example 1 in that the surface layer raw materials include surface-modified tailings machine-made sand from different sources, and the surface-modified tailings machine-made sand is prepared using Preparation Example 2.
[0078] Example 5
[0079] A fully solid waste antifreeze permeable brick, which differs from Example 1 in that the surface layer raw materials include surface-modified tailings machine-made sand from different sources, and the surface-modified tailings machine-made sand is prepared using Preparation Example 3.
[0080] Comparative Example
[0081] Comparative Example 1
[0082] A fully solid waste antifreeze permeable brick, which differs from Example 1 in that an equal amount of tailings machine-made sand is used in place of the surface-modified tailings machine-made sand in the surface layer raw materials.
[0083] Comparative Example 2
[0084] A fully solid waste antifreeze permeable brick, which differs from Example 1 in that, in the preparation method of surface-modified tailings machine-made sand of the surface layer raw material, an equal amount of γ-methacryloxypropyltrimethoxysilane is used to replace oleic acid acylpropyl dimethyl betaine and diacetone acrylamide.
[0085] Comparative Example 3
[0086] A fully solid waste antifreeze permeable brick, which differs from Example 1 in that, in the preparation method of surface-modified tailings machine-made sand of the surface layer raw material, an equal amount of oleic acid acylpropyl dimethyl betaine is used to replace γ-methacryloyloxypropyl trimethoxysilane and diacetone acrylamide.
[0087] Comparative Example 4
[0088] A fully solid waste antifreeze permeable brick, which differs from Example 1 in that, in the preparation method of surface-modified tailings machine-made sand of the surface layer raw material, an equal amount of diacetone acrylamide is used to replace γ-methacryloyloxypropyltrimethoxysilane and oleic acid acylpropyl dimethyl betaine.
[0089] Comparative Example 5
[0090] A fully solid waste antifreeze permeable brick, which differs from Example 1 in that an equal amount of water is used to replace adipic acid dihydrazide in the surface layer raw materials.
[0091] Comparative Example 6
[0092] A fully solid waste antifreeze permeable brick, which differs from Example 1 in that an equal amount of water is used to replace the acrylic polymer emulsion in the surface layer raw materials.
[0093] Comparative Example 7
[0094] A fully solid waste antifreeze permeable brick, which differs from Example 1 in that an equal amount of surface-modified tailings machine-made sand is used to replace the phase change energy storage material in the surface layer raw materials.
[0095] Performance testing
[0096] The permeable bricks obtained in Examples 1-5 and Comparative Examples 1-7 were taken as samples, and the water permeability coefficient, 28d compressive strength, 28d flexural strength, and frost resistance of the samples were tested according to GB / T28635-2012 and GB / T25993-2010. The test results are shown in Table 3.
[0097] Among them, the larger the permeability coefficient, the better the permeability; the greater the 28d compressive strength and the greater the 28d flexural strength, the better the mechanical strength; frost resistance is the compressive strength loss rate after 50 freeze-thaw cycles. The lower the compressive strength loss rate, the better the frost resistance.
[0098] Table 3 Test results
[0099]
[0100] As can be seen from Table 3, the permeable bricks of the present application have a good water permeability coefficient of 2.1-2.4 mm / s, showing good water permeability. They also have high compressive strength and flexural strength, with a 28d compressive strength of 45.6-49.2 MPa and a 28d flexural strength of 5.1-5.8 MPa, showing high mechanical strength. At the same time, they also have a low compressive strength loss rate, with a compressive strength loss rate of 3.1-3.9% after 50 freeze-thaw cycles, showing high frost resistance. The permeable bricks of the present application, through the mutual coordination of the raw materials, exhibit the characteristics of high water permeability, high mechanical strength, and high frost resistance, meeting market demand.
[0101] Example 1 is compared with Comparative Examples 1-4. In Comparative Example 1, the surface layer raw material of the tailings machine-made sand is not modified; in Comparative Example 2, the surface layer raw material of the tailings machine-made sand is modified with γ-methacryloyloxypropyltrimethoxysilane; in Comparative Example 3, the surface layer raw material of the tailings machine-made sand is modified with oleic acid acylpropyl dimethyl betaine; in Comparative Example 4, the surface layer raw material of the tailings machine-made sand is modified with diacetone acrylamide; in Example 1, the surface layer raw material of the tailings machine-made sand is modified with γ-methacryloyloxypropyltrimethoxysilane, oleic acid acylpropyl dimethyl betaine, and diacetone acrylamide. It can be seen from this that the modification of tailings machine-made sand by using γ-methacryloyloxypropyltrimethoxysilane, oleic acid acylpropyl dimethyl betaine and diacetone acrylamide at the same time, and the synergistic effect between the three can increase the compressive strength and flexural strength of permeable bricks, and reduce the compressive strength loss rate after 50 freeze-thaw cycles, so that the permeable bricks show better mechanical strength and frost resistance.
[0102] Compare Example 1 with Comparative Examples 5-6. In Comparative Example 5, no adipic acid dihydrazide was added to the surface layer raw materials; in Comparative Example 6, no acrylic acid polymer emulsion was added to the surface layer raw materials; and in Example 1, both adipic acid dihydrazide and acrylic acid polymer emulsion were added to the surface layer raw materials. This shows that the simultaneous addition of adipic acid dihydrazide and acrylic acid polymer emulsion to the surface layer raw materials can enhance the mechanical strength and frost resistance of the permeable bricks, and result in the permeable bricks exhibiting better overall performance.
[0103] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same function.
Claims
1. A full solid waste antifreeze permeable brick, characterized by: It includes a base layer and a surface layer arranged on the surface of the base layer; The base layer is mainly made of the following raw materials in parts by weight: 5-15 parts of water, 15-20 parts of cement, 2-5 parts of fly ash, 55-70 parts of waste concrete coarse aggregate, 10-15 parts of tailings machine-made sand, 0.2-0.4 parts of polypropylene fiber, and 0.1-0.3 parts of water reducer; The surface layer is mainly made of the following raw materials in parts by weight: 5-15 parts of water, 25-50 parts of cement, 3-6 parts of fly ash, 40-55 parts of surface-modified tailings machine-made sand, 1-2 parts of acrylic polymer emulsion, 0.4-0.6 parts of adipic acid dihydrazide, 10-15 parts of phase change energy storage material, and 0.1-0.3 parts of water reducer; The surface-modified tailings machine-made sand is obtained by treating tailings machine-made sand with γ-methacryloxypropyltrimethoxysilane, oleic acid acylpropyl dimethyl betaine, and diacetone acrylamide; The surface-modified tailings machine-made sand is prepared by the following method: adding γ-methacryloyloxypropyltrimethoxysilane, oleic acid acylpropyl dimethyl betaine, and diacetone acrylamide to water, mixing, then adding tailings machine-made sand, stirring for 0.5-1.5 hours, then adding ammonium persulfate, stirring for 9-11 hours, filtering, washing, and drying to obtain surface-modified tailings machine-made sand; In the surface-modified tailings machine-made sand, the weight ratio of tailings machine-made sand, γ-methacryloxypropyltrimethoxysilane, oleic acid acylpropyl dimethyl betaine, and diacetone acrylamide is 100:(2-4):(2-4):(0.5-1.5); The phase change energy storage material is one or more of phase change microcapsules MPCM5, phase change microcapsules MPCM28H, phase change microcapsules MPCM38, and phase change microcapsules MPCM48.
2. The all-solid waste antifreeze permeable brick according to claim 1, characterized in that: The phase change energy storage materials are of two types, namely phase change microcapsules MPCM5 and phase change microcapsules MPCM38, and the weight ratio of phase change microcapsules MPCM5 and phase change microcapsules MPCM38 is (1-3):(1-3).
3. The all-solid waste antifreeze permeable brick according to claim 1, characterized in that: The particle size of the waste concrete coarse aggregate is continuously graded from 1 to 10 mm; the particle size of the tailings machine-made sand is continuously graded from 0.25 to 0.5 mm.
4. The all-solid waste antifreeze permeable brick according to claim 1, characterized in that: The thickness of the base layer is 50-100 mm; the thickness of the surface layer is 5-10 mm.
5. A method for preparing all-solid waste antifreeze permeable bricks according to any one of claims 1 to 4, characterized in that: The steps include: S1. Prepare base course mixture and surface course mixture; The base mixture is prepared by the following method: water, cement, fly ash, waste concrete coarse aggregate, tailings machine-made sand, polypropylene fiber, and water reducing agent are mixed to obtain the base mixture; The surface layer mixture is prepared by the following method: water, cement, fly ash, surface modified tailings machine-made sand, acrylic polymer emulsion, adipic acid dihydrazide, phase change energy storage material, and water reducing agent are mixed to obtain the surface layer mixture; S2, pouring the base mixture into a mold, vibrating, and pressing to obtain a semi-finished product; S3. Spread the surface mixture on the surface of the semi-finished product, vibrate, press, and cure to obtain permeable bricks.
6. The method for preparing the all-solid waste antifreeze permeable brick according to claim 5, characterized in that: In step S2, the vibration frequency is 500-700 Hz, the vibration time is 3-5 s, the pressing pressure is 0.11-0.13 MPa, and the pressing time is 1-3 s; In step S3, the vibration frequency is 700-900 Hz, the vibration time is 5-7 s, the pressing pressure is 0.11-0.13 MPa, and the pressing time is 2-4 s.
7. Use of the all-solid waste antifreeze permeable brick according to any one of claims 1 to 4 in road construction.
Citation Information
Patent Citations
Coal gangue synergistic iron tailing unfired water permeable brick and preparation method thereof
CN112723840A